Enhancing physical activity during pregnancy using a multi-theory model: a study protocol for a randomised controlled trial in China - Wei Zhang; Yu Shen; Le Zhang; Ying Jin; Ningning Liu; Suwen Feng; Xuesong Zhang (BMJ Open)
Background Physical inactivity is a global concern and poses serious health risks. Physical inactivity is exacerbated and affects the health of both generations during the special period of pregnancy. Appropriate physical activity (PA) intervention programmes based on health behaviour change theory are lacking. This study aims to evaluate the effectiveness of a PA intervention based on the multi-theory model (MTM) by assessing changes in PA levels, MTM constructs, exercise self-efficacy, quality of life, prenatal depressive symptoms, gestational weight gain and pregnancy and delivery outcomes.Methods and analysis This single-centre, parallel, randomised, controlled trial will be conducted at a tertiary care institution in Hangzhou, China. A total of 72 pregnant women without contraindications to exercise at 14–27 weeks+6 days of gestation will be included. Participants will be randomly assigned to either the intervention or control group. The intervention group will engage in a 12 week PA intervention programme based on the MTM and delivered through WeChat, while the control group will receive standard antenatal care. Data will be collected at baseline, 6 weeks of the intervention, 12 weeks of the intervention and within 1 week of delivery. The primary outcomes will include PA levels measured by accelerometers and the PA in Pregnancy Questionnaire, along with the constructs of the MTM. Secondary outcomes will comprise exercise self-efficacy during pregnancy, quality of life, prenatal depressive symptoms, gestation weight gain and pregnancy and delivery outcomes. Data analysis will adhere to the Consolidated Standards of Reporting Trials 2010 statement and follow the intention-to-treat principle.Ethics and dissemination The study followed the ethical guidelines approved by the ethics committee of Women’s Hospital School of Medicine Zhejiang University (IRB-20230254-R, Approval Date: 27 July 2023). The results of the study will be submitted for publication and dissemination in a peer-reviewed journal. Participants will receive clarification regarding the study objectives, procedures and will be asked to sign informed consent in written form before the start of the study.Trial registration number ChiCTR2400080843. Prospectively registered on 8 February 2024.